AN ANALYSIS THE DIFFERENCES OF THE COMPONENTS IN ENGLISH LESSON PLANNINGS DESIGNED BY INDONESIAN AND THAILAND TEACHERS (A COMPETITIVE-DESCRIPTIVE STUDY TOWARDS ENGLISH LESSON PLANNINGS FOR SENIOR HIGH SCHOOL IN INDONESIA AND THAILAND) - Nalisa Binwang; Fegy Lestari; Restu Maulida; Iwan Dudy Gunawan (Institut Pendidikan Indonesia Garut, 2021)
The study is aimed at analyzing the differences between components in Indonesia’s and Thailand’s English lesson plantings. It is focused on finding the components that are different in four English lesson plannings. This study aims to give new knowledge and insight for Indonesian and Thai teachers to learn about the differences between one and another, and take the idea to arrange more creative and effective lesson plannings that can motivate students to learn English or other subjects for future classes. This study is a comparative-descriptive study which used Hanafiah & Suhana’s theory for Indonesia’s lesson plannings, and Chitchayawanit’s theory for Thailand’s lesson plannings. The methods used in this study are the comparative method and the descriptive method. The study has presented ten different components in English lesson plannings between Indonesia and Thailand. They are school identity, core competencies (KI), basic competencies (KD), learning standards, learner’s key competencies, desired characteristics, learning concept/essence, core content, learning method, and teaching notes. Furthermore, all of the components that have been written in Indonesia’s and Thailand’s lesson plannings are significant and have their own function and are useful for teachers when they have to design the lesson plannings for each meeting